Rumah Bulat Sebagai Markas Perjuangan Pemuda Bakumpai Marabahan Borneo Bagian Selatan (1929-1946) - Mansyur Mansyur; Hairiyadi Hairiyadi; Rusdi Effendi; Wisnu Subroto; Melisa Prawitasari; ‪Mohamad Zaenal Arifin Anis (Pendidikan IPS FKIP ULM, 2021)
The stage of Indonesian history, especially southern Borneo (Kalimantan), in the first decade of the 20th century was marked by the growth and development of nationalism. The main actors are the youngsters. From 1929-1942, there were many movement organizations with various characteristics. The organization is generally based in one headquarters. Among them are Bakumpai’s youth organizations such as the Marabahan Youth Association (PPM), the Marabahan Branch of Sarekat Islam up to the Taman Siswa School which is headquartered in Round House, Marabahan. Historical studies of the existence of round houses are still not enough. Spatial aspects (place of events) still get a small portion in local historiography. This study aims to describe the existence of Round House as the headquarters for the Marabahan Youngsters (Bakumpai) in Marabahan, Southern Borneo, in 1929 -1946. This research used a historical method with heuristics, criticism, interpretation and historiography stages. The results of the research showed that Round House is a symbolic name for the determination of the Bakumpai youngsters to fight through the organization. Originally named the Joglo Cap Crown House, as a symbol of the glory of the Bakumpai Merchant. The Cap Crown house later changed its name to Round House after becoming the headquarters of the Marabahan Youth Association and the Marabahan Branch of Islamic Sarekat in 1929. This house was also the location of the Sarekat Borneo (Kalimantan) Congress in 1930. Round House also became the school area for PHIS-Taman Siswa Branch in 1931. Due to its important position, Round House became the Headquarters of Indonesian People's Rebellion Front (BPRI) before the return of NICA to southern Borneo in 1945. This building has the status of a cultural heritage building in 2011. However, unfortunately, it is still minimally functioning as a learning resource, place or learning facility for students.